2023
DOI: 10.1128/aem.01529-22
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Prevalence Is Strongly Associated with Spatial Factors while Listeria monocytogenes Prevalence Is Strongly Associated with Temporal Factors on Virginia Produce Farms

Abstract: This study sought to examine different growing regions across the state of Virginia and to determine how factors associated with pathogen prevalence may differ between regions. Spatial and temporal data were modeled to identify factors associated with an increased pathogen likelihood in various on-farm sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
3
3
0
Order By: Relevance
“…The goal was to understand how certain soil nutrients and/or properties may synergistically and/or antagonistically affect pathogen prevalence and indicator concentrations in soil. The prevalence of Salmonella, Listeria spp., and L. monocytogenes recovered in unamended soils was low, and also similar to a previous study conducted in Virginia, which also found low Salmonella and L. monocytogenes prevalence in the agricultural soils (0.5-1.8%) (Murphy et al, 2023). Interestingly, the prevalence of foodborne pathogens in unamended soils in the study reported here is lower than pathogen prevalence in amended soils reported in previous work (Gu et al, 2019;Hailu et al, 2021;Ferguson et al, 2023;Pires et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The goal was to understand how certain soil nutrients and/or properties may synergistically and/or antagonistically affect pathogen prevalence and indicator concentrations in soil. The prevalence of Salmonella, Listeria spp., and L. monocytogenes recovered in unamended soils was low, and also similar to a previous study conducted in Virginia, which also found low Salmonella and L. monocytogenes prevalence in the agricultural soils (0.5-1.8%) (Murphy et al, 2023). Interestingly, the prevalence of foodborne pathogens in unamended soils in the study reported here is lower than pathogen prevalence in amended soils reported in previous work (Gu et al, 2019;Hailu et al, 2021;Ferguson et al, 2023;Pires et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the Salmonella serovar isolated from Farm B was not isolated from Farm C. These results suggest that diversity of Salmonella may differ by region; however, this finding may be an artifact of the small number of positive Salmonella samples in the reported study. This is supported by previous work that has shown Salmonella serovar diversity differs across regions, including interstate regions (Gorski et al, 2011;Strawn et al, 2014;Murphy et al, 2023).…”
Section: Management Practices Influenced Listeria Prevalence While Re...supporting
confidence: 85%
See 2 more Smart Citations
“…A 2020 review of agricultural water in the Southeastern United States noted that the geographical location of a water source played an important role in the prevalence and survival of foodborne pathogens ( 35 ). This conclusion is supported by other studies that compared microbial water quality between growing regions nationally ( 16 , 37 ) and locally ( 12 , 17 , 38 ), and between water types ( 32 , 39 41 ). Indeed, multiple studies have shown that this variability in water quality limits the efficacy of one-size-fits-all approaches to monitoring and mitigating microbial hazards in aquatic environments.…”
Section: Introductionsupporting
confidence: 77%